A mass-momentum consistent, Volume-of-Fluid method for incompressible flow on staggered grids. (30th January 2021) - Arrufat, T.; Crialesi-Esposito, M.; Fuster, D.; Ling, Y.; Malan, L.; Pal, S.; Scardovelli, R.; Tryggvason, G.; Zaleski, S.
Highlights: A staggered-grid method with consistent VOF mass and momentum advection. The method is tested for a droplet without surface tension in uniform flow. Tested for a droplet suddenly accelerated at very large density ratio up to 10 9 . Comparison with theoretical results for the Kelvin-Helmholtz instability given. Detailed analysis of a 3mm-diameter falling raindrop is given. Abstract: The computation of flows with large density contrasts is notoriously difficult. To alleviate the difficulty we consider a discretization of the Navier-Stokes equation that advects mass and momentum in a consistent manner. Incompressible flow with capillary forces is modeled and the discretization is performed on a staggered grid of Marker and Cell type. The Volume-of-Fluid method is used to track the interface and a Height-Function method is used to compute surface tension. The advection of the volume fraction is performed using either the Lagrangian-Explicit / CIAM (Calcul d'Interface Affine par Morceaux) method or the Weymouth and Yue (WY) Eulerian-Implicit method. The WY method conserves fluid mass to machine accuracy provided incompressibility is satisfied. To improve the stability of these methods momentum fluxes are advected in a manner "consistent" with the volume-fraction fluxes, that is a discontinuity of the momentum is advected at the same speed as a discontinuity of the density. To find the density on the staggered cells on which the velocity is centered, an auxiliary reconstruction of the density is performed. The method is tested for a droplet without surface tension in uniform flow, for a droplet suddenly accelerated in a carrying gas at rest at very large density ratio without viscosity or surface tension, for the Kelvin-Helmholtz instability, for a 3mm-diameter falling raindrop and for an atomizing flow in air-water conditions.